Penerapan Writing Workshop untuk Meningkatkan Keterampilan Menulis Teks Deskripsi Mahasiswa PGSD Universitas Mataram - Heri Setiawan; Awal Nur Kholifatur Rosyidah; Syaiful Musaddat (Pendagogia: Jurnal Pendidikan Dasar, 2025)
The purpose of this study is to improve the descriptive text writing skills of PGSD FKIP Mataram University students through the application of writing workshop strategies. This research uses an action research approach with four main stages: planning, action, observation, reflection, and planning revision. The subjects of this study were 32 third-semester PGSD FKIP Mataram University students in the 2018/2019 academic year. Data collection techniques used interviews, performance tests, and observations. The instruments used were interview guidelines, descriptive text assessment instruments, and observation sheets. The results of the study showed that the application of writing workshop strategies in the Indonesian Language Skills course for Elementary Schools had a positive impact. 20 (63%) students achieved the Minimum Completion Criteria (KKM) in cycle I and 27 (84%) students achieved the Minimum Completion Criteria (KKM) in cycle II.